Inhibition of Notch Signaling in Combination with Paclitaxel Reduces Platinum-Resistant Ovarian Tumor Growth - Groeneweg, Jolijn W.; DiGloria, Celeste M.; Yuan, Jing; Richardson, William S.; Growdon, Whitfield B.; Sathyanarayanan, Sriram; Foster, Rosemary; Rueda, Bo R. (Frontiers in Oncology, 2014)
Introduction: Ovarian cancer (OvCa) is the most lethal gynecologic malignancy in the United States because of chemoresistant recurrent disease. Our objective was to investigate the efficacy of inhibiting the Notch pathway with a gamma-secretase inhibitor (GSI) in an OvCa patient derived xenograft (PDX) model as a single agent therapy and in combination with standard chemotherapy. Methods: Immunocompromised mice bearing xenografts derived from clinically platinum sensitive human ovarian serous carcinomas were treated with vehicle, GSI (MRK-003) alone, paclitaxel and carboplatin (P/C) alone, or the combination of GSI and P/C. Mice bearing platinum resistant xenografts were given GSI with or without paclitaxel. Gene transcript levels of the Notch pathway target Hes1 were analyzed using RT-PCR. Notch1 and Notch3 protein levels were evaluated. The Wilcoxon rank-sum test was used to assess significance between the different treatment groups. Results: Expression of Notch1 and 3 was variable. GSI alone decreased tumor growth in two of three platinum sensitive ovarian tumors (p < 0.05), as well as in one of three platinum sensitive tumors (p = 0.04). The combination of GSI and paclitaxel was significantly more effective than GSI alone and paclitaxel alone in all platinum resistant ovarian tumors (all p <0.05). The addition of GSI did not alter the effect of P/C in platinum sensitive tumors. Interestingly, although the response of each tumor to chronic GSI exposure did not correlate with its endogenous level of Notch expression, GSI did negatively affect Notch signaling in an acute setting. Conclusions: Inhibiting the Notch signaling cascade with a GSI reduces primary human xenograft growth in vivo. GSI synergized with conventional cytotoxic chemotherapy only in the platinum resistant OvCa models with single agent paclitaxel. These findings suggest inhibition of the Notch pathway in concert with taxane therapy may hold promise for treatment of platinum resistant OvCa.